The relative importance of sociocognitive factors in Lebanese adolescents' career indecision - Mogharbel, Jamileh Anas (Beirut American University of Beirut. Faculty of Arts and Sciences, 2012)
Previous research on Lebanese adolescents has shown that Lebanese students lack career maturity and often make uninformed career decisions (Fleihan, 2010; Moracco, 1976; Theodory, 1982). The Social Cognitive Career Theory (SCCT; Lent et al., 1994; 2000) posits that the career decision-making process is the result of a dynamic interaction amongst various personal, cognitive and contextual variables. The purpose of this study was twofold: to determine the relative importance of various contextual, individual and cognitive variables associated with SCCT in predicting Lebanese adolescents career indecision and to compare the decision-making processes of students with low career indecision to those with high career indecision. A mixed-methods design was employed in which questionnaires and semi-structured interviews were used as data collection tools. Participants included 420 students ranging from grades 8 to 12 who were taken from two public and two private schools from Beirut and its suburbs. Multiple regression analyses revealed that the contextual variables, particularly students perceptions of barriers and parental support, were the two most important predictors of students career indecision while the cognitive and individual variables did not have a large impact. Findings of the regression analyses also suggested important gender and grade level differences. Student interviews provided additional support for the regression analyses and further suggested that although there are differences between the decision-making processes of high and low career indecision students, students of both indecision levels seem to make premature decisions. Recommendations for future research and implications for practice are discussed.
: Mémoire
Keywords: Adolescents; Adolescents; Milieu Socio-Culturel; Socio-Cultural Milieu